Civics as Applied Sociology - Weinstein, Jay (Social justice, 2003)
Part of a special issue on applied research and social justice. The relationship in civil society between democracy and applied sociology is discussed. It is argued that although not inherently committed to democracy, sociological thinking and technique are inclined to support prodemocratic partisanship.